Frontispiece: Interplay of Polarity and Confinement in Asymmetric Catalysis with Chiral Rh Diene Complexes in Microemulsions. Issue 68 (7th December 2021) - Kirchhof, Manuel; Abitaev, Karina; Abouhaileh, Abdulwahab; Gugeler, Katrin; Frey, Wolfgang; Zens, Anna; Kästner, Johannes; Sottmann, Thomas; Laschat, Sabine
Abstract : The influence of anionic and cationic co‐surfactants in nonionic microemulsions on the performance of chiral Rh‐norbornadiene complexes with different counterions in the 1, 2‐addition of phenylboronic acids to N ‐tosylimines is described. Catalytic studies revealed the unique role of the counterion and the type of co‐surfactant. NMR experiments and the calculated intrinsic binding orbitals suggest that the anion exchange with co‐surfactant accelerates the formation of the catalytically active Rh‐OH complex, thus increasing the yield and affecting the enantioselectivity. For more information, see the Full Paper by M. Kirchhof, K. Abitaev and co‐workers on page 16853 ff .